10.B. Workshop: Corporate influence on science – what is happening and what can be done?. (30th September 2020) - ,; ,
Abstract: The role of the corporate sector in research sponsorship is growing. So too is the evidence that corporations whose products are potentially damaging to health or the environment influence science and the ways in which science is used in policy and practice. Such efforts are a key part of corporate attempts to maintain or increase the consumption or use of industry products, and to secure favourable policy outcomes. The products and practices of corporations are responsible for a growing proportion of the global disease burden. Non-communicable diseases, many driven by consumption of unhealthy commodities and exposure to chemicals, account for over 73 percent of global deaths. It is increasingly important to understand the complex and multifaceted ways corporations seek to influence science; the impact these strategies have; and the ways this influence can be addressed. This workshop brings together global experts to explore these issues. Drawing on examples from several industries (e.g. tobacco, alcohol, food, and pharmaceuticals), it aims to: Increase understanding of the ways corporations whose products are potentially damaging to health influence science. We present a newly developed, evidence-based typology which draws together the vast existing literature in this field, to present a simplified way of understanding corporate influence on science. Delegates will be provided with materials that provide a means for recognising such influence. Examine the influence that corporations have on the first stage in the research process - research agendas. We present examples from tobacco, food and pharmaceutical industries which illustrate the mechanism through which industry funding of science drives researchers to study questions that are favourable to industry. The desired outcome is to maximise research on the benefits of industry products (positioning these products as solutions to complex problems), minimise research on the harms of their products, support their policy and legal positions, and impede potential regulation of their products. Increase awareness of the involvement that corporations have had in altering the mechanisms though which science is used in policymaking. Delegates will hear how corporations promoted and embedded policymaking reforms which increase reliance on and provide a conduit for industry-favourable science. Suggest ways forward concerning management of conflicts of interest in the publication of health research. Here we will discuss the roles that journals can play in governing conflicts of interest and issues of transparency in the publication of academic research. Suggest ways forward for funding research on unhealthy commodities. We present criteria for tobacco industry-supported research funding programs, and discuss the applicability of similar programs for funding research on other unhealthy commodities, and on the practices of other industries such as the fossil fuels industry. Key messages: Corporations have been seen to skew evidence bases, manipulate interpretations of science, and influence use of science in policy and practice – such influence is a major threat to public health. This workshop exposes industry tactics in this area and begins to identify ways for dealing with them.